Nanotubos de titanatos e sua aplicação em matrizes de poliuretano - Monteiro, Wesley Formentin (2015)
The search for improvements in the properties of polymer matrices has been the subject of several studies. Among these, the use of inorganic fillers has shown results that demonstrate improvements in many properties of the polymers. In this context, this study aimed to preparation of titanates nanotubes (TNT) and its application in polyurethane nanocomposites (PU). In order to the TNT were synthesized from commercial TiO2 in anatase phase by hydrothermal method. After, these TNT were functionalized (TNTF) with hexamethylene diisocianato (HDI) and silanes compounds: aminopropyl trimethoxysilane (APTMS) and tetraethyl orthosilicate (TEOS) in order to study the interaction of the functionalizated charge with the polymer matrix. The titanates nanotubes (TNT) and titanates nanotubes functionalized (TNTF) were characterized regarding their morphological and structural properties. Nanocomposites of PU with TiO2, TNT and TNTF were synthesized, via in situ polymerization and characterized by FTIR, GPC, SEM, TEM (just NTT), AFM, TGA, DSC and DRX techniques. The results showed that the TNT synthesis by hydrothermal method was effective and was obtained nanotubes formed with a minimum of 3 staked sheets. The TNTF functionalized with APTMS and TEOS showed clustered structures whereas with HDI has a separation of nanotubes. The addition of TNT-HDI provided an increase of polymer molar weight. All nanocomposites showed higher thermal stability (between 330-340oC) than the pure PU (325oC). Nanocomposites PU/TNTF presented the highest values for crystallization temperature (≈ 6-10oC) when compared to pure PU (5oC), besides of its enthalpies, indicating that TNTF promote the increase of the polyurethane crystallinity.